The effect of a categorical discrimination task on the auditory M100-peak latency - König, R.; Sieluzycki, C.; Simserides, C.; Scheich, H. (International Congress Series, 2007)
The rationale of this magnetoencephalographic (MEG) study was the quest for temporal aspects of the fMRI-characterized hemispheric asymmetries of auditory cortex functions during the processing of simple linearly frequency-modulated (FM) tones. We searched for parameters which distinguish a stimulus-related task condition—the categorical discrimination of direction (upward versus downward) of frequency modulation—from mere exposure to the same FM tones. We found that the M100-peak latency after FM tones was significantly shorter in the task condition than in the exposure condition, in the left but not in the right hemisphere.